Valorization of carbohydrates: dehydration of sorbitol to isosorbide in the presence of acidic zeolites - Santamaría-González, José; Lerena Gil, Isabel; Ginés-Molina, María José; Mérida-Robles, Josefa María; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2015)
Currently, the growing interest in the use of biomass as a renewable and sustainable raw material for the production of energy, chemicals and biofuels is driving the development of new catalytic processes and technologies for its conversion. In this context, the transformation of lignocellulosic biomass can lead to a variety of platform chemicals, with a broad spectrum of applications. Sorbitol is one of the useful biomass-derived chemicals that is obtained by catalytic hydrogenation of glucose, which subsequent dehydration and intramolecular cyclization in acid medium gives rise to the formation of isosorbide. This is a high value-added chemical widely used as intermediate in the pharmaceutical industry, additive polymers such as polyethylene terephthalate (PET) and production of biodegradable polymers. Mineral acids such as sulphuric and hydrochloric acids have efficient catalytic properties for dehydration of sorbitol. However, the well-known drawbacks associated to homogeneous catalysis have promoted the studies of heterogeneous catalytic processes. Thus, solid acid catalysts such as zeolites, tetravalent metal phosphates and sulfated copper oxide have been reported as alternative solid catalysts. Nevertheless, sometimes, drastic experimental conditions are required to reach a high catalytic activity. In the present work, different commercial zeolites, in their protonic form, have been evaluated as acid solid catalysts for sorbitol dehydration, and several experimental variables have been optimized
Keywords: Catálisis heterogénea; Sorbitol; Heterogeneous catalysis; Dehydration; Isosorbide; Zeolitas